PROTOCOL: Health, social care and technological interventions to improve functional ability of older adults: Evidence and gap map. Issue 4 (10th October 2019) - Welch, Vivian; Howe, Tracey E.; Marcus, Sue; Mathew, Christine M.; Sadana, Ritu; Rogers, Morwenna; Sheehy, Lisa; Borg, Johan; Pottie, Kevin; Thompson‐Coon, Joanna; Lyddiatt, Anne; Kristjansson, Elizabeth; et al.
Abstract: This is a protocol for a Campbell Evidence and Gap Map. The objectives are to identify and assess the available evidence on health, social care and technological interventions to improve functional ability among older adults.